MEMORY TYPES AND IDENTITY IN THE DINKO ŠIMUNOVIĆ'S NOVEL MLADI DANI (Philological Studies, 2019)
Mladi dani, Šimunović's autobiographical novel focuses on the individual who tryes to determine his own identity. This is significante because it represents the connection with the identity of his whole group. The collective reveals the specific world of interaction amoung its members. The purpose is to evoke the heroic past of ancestors and the efforts to store it within the memory of future generations. Šimunović's style of writing is filled with examples of the same. Cultural memory is also important. It distinguishes the every day and spiritually higher realities. Ethnic connection is extremly strong. The group's identity serves as defence from external influences while consolidating its own authencity. Consequently, the purpose of this essay is to illustrate the significance of Šimunović's autobiographic prose Mladi dani within the context of memory studies. The phennomennon of memory coresponds with origin/identity of individual and his community at the same time. It also helps significantly nurturing the word-of-mouth literary tradition.
Keywords: memory, autobiographical memory, collective memory, cultural memory, identity, oral Croatian literature